Vengeance moon - West, Charles (Waterville, Me. : Thorndike Press, 2007)
On the run for a murder he didn't commit, Matt Slaughter is lying low in the badlands with a new life, and a new woman. But old troubles are right behind him: her name is P.D.Wildmoon, a hard-drinking bounty huntress armed with a .44, a rawhide horsewhip, and three wild-eyed sons bred to kill. The job? Bring the fugitive back to Virginia-dead or alive.
90550
Keywords: Large type books; Western stories